Q. 63.7( 3 Votes )

<span lang="EN-US

Answer :

To find: Differentiation of (x2 + 3x + 1) sin x


Formula used: (i) (uv)′ = u′v + uv′ (Leibnitz or product rule)


(ii)


(iii)


Let us take u = x2 + 3x + 1 and v = sin x




Putting the above obtained values in the formula :-


(uv)′ = u′v + uv′


[(x2 + 3x + 1) sin x]’ = (2x + 3) × sinx + (x2 + 3x + 1) × cosx


= sinx (2x + 3) + cosx (x2 + 3x + 1)


Ans) (2x + 3) sinx + (x2 + 3x + 1) cosx


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

If f(x) = x sin xRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

Differentiate theRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

DifferentiaRS Aggarwal - Mathematics